Urinary Tract Infections (UTI) Among Patients at G.G. Hospital & Medical College, Jamnagar - Shirishkumar Patel; Pankajkumar P Taviad; Mala Sinha; T B Javadekar; Vipul P Chaudhari (Medsci Publications, 2012)
Background: It has been estimated that symptomatic urinary tract infections (UTI) occurs in as many as 7 million visits to emergency units and 100,000 hospitalizations annually. UTI has become the most common hospital-acquired infection, accounting for as many as 35% of nosocomial infections, and it is the second most common cause of bacteraemia in hospitalized patients. Objective: (1) To detect the prevalence rate of bacterial infection among urinary isolates from patients having UTI. (2) To detect prevalence rate of drug resistance among pathogen isolate from patients having UTI. Results: The prevalence of Urinary Tract Infections (UTI) was evaluated in 3046 patients attending G.G. Hospital & Medical College, Jamnagar. Results showed 1416 (46.48%) patients were positive. The most common organisms were Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Proteus mirabilis. In-vitro antibiotic susceptibility tests revealed that the gram negatives bacteria were sensitive to quinolones (Gatifloxacin, levofloxacin) and meropenum, while the gram positive isolates were sensitive to linazolid, erythromycin & quinolones (Gatifloxacin, levofloxacin ). Conclusion: The findings suggested the need for constant monitoring of susceptibility of specific pathogens in different populations to commonly used anti-microbial agents.